Analytical models of the mechanical properties of Japanese larch (Larix kaempferi (Lamb.) Carr.) based on non-destructive testing and visual grading parameters. Issue 2 (4th March 2021) - Barriola, M. J.; Aira, J. R.; Villanueva, J. L.
ABSTRACT: Increasing concern about the rapid proliferation of fungi attacking stands of radiata pine in the north of the Iberian Peninsula has led to a search for alternative conifer species that would be able to replace the affected trees. In this context one of the candidate species is the Japanese larch, a species that has not been structurally characterised within Spanish standards. This study describes several analytical models which make it possible to estimate the strength and rigidity variables of this species, using a combination of non-destructive testing techniques and visual grading parameters. Models were obtained by multiple regressions to estimate the global elasticity modulus (MOEG) and the local elasticity modulus (MOE), including and excluding correction for moisture content. The modulus of rupture (MOR) was also calculated while including and excluding correction for size. When the analytical models were subjected to the relevant corrections they were all less accurate. Estimation of the MOEG ( r 2  = 0.66) was slightly more accurate than estimation of the MOE ( r 2  = 0.56), and it was far more accurate than estimation of the MOR ( r 2  = 0.44).